2010
DOI: 10.7196/samj.3235
|View full text |Cite
|
Sign up to set email alerts
|

Cancer prevalence in 129 breast-ovarian cancer families tested for BRCA1 and BRCA2 mutations

Abstract: Breast cancer is the most common malignancy among women in South Africa, with a crude incidence rate of 18.5/100 000 recorded between 1993 and 1995.1 A small but significant percentage (5 -10%) of breast cancer cases are directly due to an inherited susceptibility.2 Two tumour suppressor genes involved in early-onset breast and ovarian cancer, BRCA1 and BRCA2, have been mapped and cloned. 3,4 These two genes explain 20 -40% of heritable breast cancer cases in various populations over the world. 5,6 A large lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…Some cancer incidence studies have found a significantly increased risk for a variety of other cancers, including stomach, pancreatic and melanoma [10]. Differences between the results suggest population and mutation specificity.…”
Section: Hereditary Breast and Ovarian Cancer Syndromementioning
confidence: 48%
See 4 more Smart Citations
“…Some cancer incidence studies have found a significantly increased risk for a variety of other cancers, including stomach, pancreatic and melanoma [10]. Differences between the results suggest population and mutation specificity.…”
Section: Hereditary Breast and Ovarian Cancer Syndromementioning
confidence: 48%
“…In most studies the family members of mutation positive women reported a significantly higher incidence of uterine cancer than the probands of mutation negative women [10]. One large study based on family history of 11 000 women, reports the risk for uterine cancer as 2.65 times the background population risk [51] Although many case reports of uterine and uterine papillary serous carcinoma (UPSC) in mutation positive women have been published and women diagnosed with UPSC seem to have a family history suggestive of HBOC more often than expected [55], the risk in genetically predisposed women to develop these cancers seem relatively low.…”
Section: Uterine Cancermentioning
confidence: 99%
See 3 more Smart Citations